Locus of Control and Its Relationship with Motivation: Mediated by Grit - Torres, Jennifer; Chen, Daniel; Peixoto, Beatriz (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the relationship between locus of control and academic motivation among adolescents, with grit examined as a potential mediating variable. Methods and Materials: The study employed a descriptive correlational design and was conducted among 380 high school students in Canada, selected based on the Morgan and Krejcie sample size table. Participants completed three standardized instruments: the Rotter Internal-External Locus of Control Scale, the Short Grit Scale (Grit-S), and the Academic Motivation Scale (AMS). Data were analyzed using SPSS-27 to compute descriptive statistics and Pearson correlation coefficients, while Structural Equation Modeling (SEM) was performed using AMOS-21 to evaluate the mediating effect of grit and assess the fit of the proposed model. Findings: Descriptive analysis showed that the mean scores were 12.86 (SD = 3.47) for locus of control, 3.62 (SD = 0.58) for grit, and 5.14 (SD = 0.76) for academic motivation. Pearson correlations revealed significant positive relationships between all variables: locus of control and grit (r = .41, p < .001), grit and motivation (r = .47, p < .001), and locus of control and motivation (r = .36, p < .001). SEM results indicated a good model fit (χ²/df = 1.90, CFI = 0.97, RMSEA = 0.048). Grit significantly mediated the relationship between locus of control and motivation, with both direct (β = .25, p = .002) and indirect effects (β = .18, p < .001) being statistically significant. Conclusion: The findings suggest that adolescents with an internal locus of control tend to demonstrate higher grit, which in turn enhances their academic motivation. Grit functions as a key psychological mechanism that strengthens the influence of control beliefs on motivational outcomes, indicating its importance in educational development and intervention planning.